E-Dictionary of Basic Barong Dance Based on Direct Instruction in SBdP Subjects for Deaf Students - I Putu Widiyana Putra; Anak Agung Gede Agung; Ni Luh Putu Agetania (Universitas Pendidikan Ganesha, 2025)
This research is based on the problem that there is no learning media that can help deaf students in improving their skills so that their learning outcomes at school are still not optimal. The purpose of this research is to produce digital learning media, namely E-Dictionary of basic Barong dance based on direct instruction which has been adapted to the characteristics of deaf children. The type of research conducted is development research with the ADDIE model with the subjects involved, namely design experts, learning content experts, instructional design experts, learning media experts, and 6 deaf students in third grade. The data in this study were collected by non-test methods in the form of distributing questionnaires and performance assessments. Data analysis techniques used are descriptive qualitative, descriptive quantitative, and inferential statistics. The results of this study obtained a design expert assessment of 95.45%, learning content experts of 95%, instructional design experts of 95%, learning media experts of 95%, individual trials of 93.75%, small group trials of 95.48% which were qualified as very good. Based on the dependent sample t test, tcount = 17.855 was obtained. These results show tcount = 17.855 > ttable = 2.571. So it can be concluded that E-Dictionary of basic Barong dance based on direct instruction is effectively applied to SBdP subjects of deaf students in third grade. The implication of this research is to motivate teachers to use the E-Dictionary of basic Barong dance based on direct instruction in SBdP learning for deaf students.